What determines Chinese outward direct investment in Africa? Case study: CNPC and Huawei - WU, XUANYONG (2014)
Outward foreign direct investment (OFDI) from China has increased substantially in recent years. Africa, as one of the most significant destinations of OFDI, has attracted increased global attention. The determinants of China’s OFDI to Africa are primarily linked to poorly governed countries with abundant natural resources. However, the results are inconclusive because of the differences between state-controlled and privately owned firms. In order to explore what drives Chinese OFDI in Africa, this study will focus on the determinants of OFDI based on the ownership of firms. Much research is concerned with the determinants of China’s OFDI, but there is little focus on FDI in Africa. The significance of this research is that it pays more attention to the region of Africa, which is good for comprehensively examining China’s OFDI and avoiding misunderstandings, for example that China is simply ‘a ravenous dragon’ when it comes to resources. Using descriptive analyses and case studies, it can be found that the determinants of China’s OFDI in Africa differ based on ownership. State controlled firms are attracted to countries with large sources of natural resources and risky political environments, but the market-seeking is the main motivation of private enterprises. In addition, government involvement is considered as one of the most significant drivers of OFDI to influence Chinese firms. It explains why Chinese firms without conventional types of competitive advantages similar to their developed country counterparts can still expand overseas. The findings also show that existing internationalization theories cannot substantially explain the FDI of Chinese firms. This study is a valuable addition to the growing literature on China’s OFDI and provides important advice to Chinese policy makers and Chinese investors.